Nutritional profiling and shelf life assessment of monosex tilapia steaks during ice storage - Parvathy, U.; Raushan, S. Mohammed; Ninan, George; Jeyakumari, A.; Lalitha, K. V.; Mathew, Suseela; Zynudheen, A. A. (Indian Journal of Fisheries, 2016)
In freshwater aquaculture, monosex tilapia is emerging as a potential alternative to common tilapia which is a prolific breeder. The nutritional profile as well as the shelf-life stability of monosex tilapia stored under iced condition was assessed. The fatty acid profile pointed out that the major class of fatty acids present in tilapia was monounsaturated fatty acids (42.36%). Amino acid compositional analysis indicated higher levels of glutamic acid and aspartic acid. Tilapia steaks were divided into two lots for ice storage viz., control (AP: air packed) and vacuum packed (VP). AP samples crossed the total volatile base nitrogen (TVB-N) acceptability limit of 35 mg% towards 16th day of storage whereas VP samples were acceptable throughout the storage period of 19 days. Increase in thiobarbituric acid (TBA) value was more prominent in air packed lots during storage period. The decrease in hardness and lightness values were more prominent in vacuum packed samples. Results of the biochemical and microbiological analyses indicated that air packed samples were acceptable upto 16th day while it was extended to 19th day in vacuum packed samples.